Framework for an integrated system for enhancing the energy efficiency and structural performance of buildings - Votsis, Renos; Tantele, Elia; Kyriakides, Nicholas; Christofe, Andreas; Chrysostomou, Christis (My University, 2018)
The building stock should be in operational and reliable state in order to ensure primarily the safety of the users. In addition to safety, nowadays the comfort of the users is of prime importance. To satisfy the required comfort levels the user should consume energy, in the form of heating, cooling etc. Therefore this ongoing trend to satisfy these conditions, results in buildings which are safer, more economic to operate and more sustainable. Taking into account economic, technical, durability and environmental factors there is the need for a holistic approach for the optimum performance of buildings for structural integrity and energy efficiency. Current practice evolves around building solutions that isolate each deficiency and proposes solutions to enhance each of the two separately. In the last few years, from a sustainability perspective, emphasis is placed on developing an integrated system for buildings that will improve simultaneously both the structural integrity and the energy performance and should be preferred over individual actions. This study investigates independent building and/or retrofit actions applied for structural strengthening and energy performance improvements that have the potential to be combined into an integrated system to enhance the overall performance of buildings. Such multidisciplinary approach will ensure that new and existing buildings satisfy both structural safety and energy efficiency targets in a more economic and effective manner. Furthermore, as first step in this direction, an experimental test program was conducted in the laboratory to examine the benefit of applying thermal insulation in the form of polystyrene on the durability context by reducing the building's material deterioration due to environmental effects.